Effect of Hypercholesterolemia on Fatty Infiltration and Quality of Tendon-to-Bone Healing in a Rabbit Model of a Chronic Rotator Cuff Tear: Electrophysiological, Biomechanical, and Histological Analyses. (May 2016) - Chung, Seok Won; Park, HaeBong; Kwon, Jieun; Choe, Ghee Young; Kim, Sae Hoon; Oh, Joo Han
Background: The incidence of healing failure after rotator cuff repair is high, and fatty infiltration is a crucial factor in healing failure. Purpose: To verify the effect of hypercholesterolemia on fatty infiltration and the quality of tendon-to-bone healing and its reversibility by lowering the cholesterol level in a chronic tear model using the rabbit supraspinatus. Study Design: Controlled laboratory study. Methods: Forty-eight rabbits were randomly allocated into 4 groups (n = 12 each). After 4 weeks of a high-cholesterol diet (groups A and B) and a regular diet (groups C and D), the supraspinatus tendon was detached and left alone for 6 weeks and then was repaired in a transosseous manner (groups A, B, and C). Group D served as a control. Group A continued to receive the high-cholesterol diet until the final evaluation (6 weeks after repair); however, at the time of repair, group B was changed to a general diet with administration of a cholesterol-lowering agent (simvastatin). Histological evaluation of the fat-to-muscle proportion was performed twice, at the time of repair and the final evaluation, and an electromyographic (EMG) test, mechanical test, and histological test of tendon-to-bone healing were performed at the final evaluation. Results: For the EMG test, group A showed a significantly smaller area of compound muscle action potential compared with groups C and D (all P < .01), and group B showed a larger area than group A, almost up to the level of group C ( P = .312). Similarly, group A showed significantly lower mechanical properties both in load-to-failure and stiffness compared with groups C and D (all P < .05). In addition, although not significantly different, the mechanical properties of group B were higher than those of group A (mean load-to-failure: group A = 42.01 N, group B = 58.23 N [ P = .103]; mean stiffness: group A = 36.32 N/mm, group B = 47.22 N/mm [ P = .153]). For the histological test, groups A and B showed a significantly higher fat-to-muscle proportion than did groups C and D at 6 weeks after detachment (all P < .05), but at the final evaluation, group B showed a decreased fat-to-muscle proportion (mean ± SD: from 64.02% ± 11.87% to 54.68% ± 10.47%; P = .146) compared with group A, which showed increased fat-to-muscle proportion (from 59.26% ± 17.80% to 78.23% ± 10.87%; P = .015). Groups B and C showed better tendon-to-bone interface structures than did group A, which showed coarse and poorly organized collagen fibers with fat interposition. Conclusion: Hypercholesterolemia had a deleterious effect on fatty infiltration and the quality of tendon-to-bone repair site, and lowering hypercholesterolemia seemed to halt or reverse these harmful effects in this experimental model. Clinical Relevance: Systemic diseases such as hypercholesterolemia should be tightly controlled during the perioperative period of rotator cuff repair.